Correlation Between Fecal Metabolomics and Gut Microbiota in Obesity and Polycystic Ovary Syndrome - Zhou, Ling; Ni, Zhexin; Yu, Jin; Cheng, Wen; Cai, Zailong; Yu, Chaoqin (Frontiers in Endocrinology, 2020)
Objective: This study aimed to explore the relationship between the fecal metabolites and gut microbiota in obese patients with PCOS and provide a new strategy to elucidate the pathological mechanism of obesity and PCOS. Methods: The fecal samples of obese patients with PCOS (n = 18) and obese women without PCOS (n = 15) were analyzed by 16S rRNA gene sequencing and untargeted metabolomics. The peripheral venous blood of all subjects was collected to detect serum sex hormones. The association among fecal metabolites, gut microbiota, and serum sex hormones was analyzed with the R language. Results: A total of 122 named differential fecal metabolites and 18 enrichment KEGG pathways were obtained between the groups. Seven fecal metabolites can be used as characteristic metabolites with an area under curve of ROC analysis of > 0.8 in the obese patients with PCOS, including DHEA sulfate. The richness and diversity of gut microbiota in the obese PCOS group were lower than those in the control group. Lachnoclostridium, Fusobacterium, Coprococcus_2, and Tyzzerela 4 were the characteristic genera of the obese patients with PCOS. Serum T level significantly and positively correlated with the abundance of fecal DHEA sulfate (p < 0.05), and serum DHEAS level significantly and negatively correlated with the abundance of fecal teasterone (p < 0.05). Conclusion: Specific fecal metabolites may be used as characteristic metabolites for obese patients with PCOS. The closely relationship among gut microbiota, fecal metabolites, and serum sex hormones may play a role in the related changes caused by hyperandrogenemia.